Ціна свободи - Філіпчук, П. П.; Сергієва, А. В. (ХНУРЕ, 2020)
Today, when it comes to the formation and preservation of Ukraine's statehood, we are increasingly faced with the question: “Who are we? Where? What are we? How have our long-suffering people lived throughout their history?”
Keywords: українська державність; українознавство